Customer Insights that drive innovative social enterprises - Steffen Schmidt; Frederik Niedernolte; Levke Albertsen; Carina de Lopez; Philipp Reiter; Sascha Langner (Marketing Review St.Gallen, 2017)
The transformation of societies is the core business of innovative social enterprises. These hybrid organizations require deep customer insights to address the manifold needs of the public and business. The present work shows how marketing research enhanced the marketing intelligence of the social enterprise known as Little Sun, enabling the company to better promote its latest innovative product that uses "the power of sustainable light and energy to transform lives".
Keywords: 650